2020
DOI: 10.1021/jacs.9b11528
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Dimensional Poly(azatriangulene) Covalent Organic Framework with Semiconducting and Paramagnetic States

Abstract: The black crystalline (aza)­triangulene-based covalent organic framework TANG-COF was synthesized from its trinitro-TANG precursor via a one-pot, two-step reaction involving Pd-catalyzed hydrogenation and polycondensation with an aromatic dialdehyde. High crystallinity and permanent porosity of the layered two-dimensional (2D) structure were established. The rigid, electron-rich trioxaazatriangulene (TANG) building block enables strong π-electron interactions manifested in broad absorptions across the visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 49 publications
4
97
0
Order By: Relevance
“…We previously reported that radical‐substituted donor NN‐TOT produced stable radical‐substituted radical cation salts upon selective oxidation of the donor unit due to the superior electron‐donating nature of TOT (Figure 1). [5,10,11] Importantly, the diradical cationic species, NN‐TOT + is indicated as being present in the triplet ground state with quite large intramolecular exchange interactions. In addition, diradial cation salt NN‐TOT + ⋅ GaCl 4 − exhibited a magnetic phase transition at T =2.65 K from a short‐range‐ordered antiferromagnetic chain to a three‐dimensional weak ferromagnet [5] .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that radical‐substituted donor NN‐TOT produced stable radical‐substituted radical cation salts upon selective oxidation of the donor unit due to the superior electron‐donating nature of TOT (Figure 1). [5,10,11] Importantly, the diradical cationic species, NN‐TOT + is indicated as being present in the triplet ground state with quite large intramolecular exchange interactions. In addition, diradial cation salt NN‐TOT + ⋅ GaCl 4 − exhibited a magnetic phase transition at T =2.65 K from a short‐range‐ordered antiferromagnetic chain to a three‐dimensional weak ferromagnet [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they found that doped P11 showed a paramagnetic property under cryogenic conditions. 63 Triazine-containing conjugated polymers have been promising for versatile applications due to their nitrogen-rich optoelectronic nature. The traditional synthetic methods require the monomers to bear a high temperature or strong acid treatment, which limits the choices of monomers.…”
Section: Exfoliation From Layered Bulk Polymersmentioning
confidence: 99%
“…(e and f) Temperature dependence of (e) the spin susceptibility and (f) the ESR line width. Reprinted with permission from ref 63,. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%
“…Formation of "hole" polarons in organic materials, optically (e.g., by photoinduction), electrochemically (e.g., by applying gate voltage) or in the presence of chemical dopants, gives rise to significant absorption in the mid-IR energy range, which is characterized by a lowenergy peak A (0.05-0.2 eV), dressed with intramolecular vibrations (IRAVs), and a much broader higher energy peak B (> 0.25 eV ). [25][26][27][28][29][30][31] The A peak is labelled as DP 1 (delocalized polaron) 26,32 or CT (charge transfer), 25,33,34 while the B peak is commonly referred to as P1 25,26,30 in the conventional polaron model. In conjugated polymers, such as P3HT, a redshift of peak B(P1) is either related to increased polaron delocalization lengths [26][27][28]30,35 or the formation of spin-less non-radical bipolarons.…”
Section: Introductionmentioning
confidence: 99%
“…37 The characteristic low energy-peak A and the blue-shifted broad peak B is evident in the mid-IR absorption spectra of iodine doped (aza)triangulene-based COF (TANG-COF) which exhibit high inand out-of-plane conductivity. 31 COFs exhibit a dramatic but reversible increase in conductivity upon exposure to iodine. 11,[38][39][40] Vapor doping tetrathiafulvalene-based COFs with iodine results in a significantly larger increase in conductivity compared to solution doping with TCNQ.…”
Section: Introductionmentioning
confidence: 99%